Understanding autonomous behaviour development: Exploring the developmental contributions of context‐tracking and task selection to self‐directed cognitive control. Issue 4 (6th January 2022) - Frick, Aurélien; Brandimonte, Maria A.; Chevalier, Nicolas
Abstract: Gaining autonomy is a key aspect of growing up and cognitive control development across childhood. However, little is known about how children engage cognitive control in an autonomous (or self‐directed) fashion. Here, we propose that in order to successfully engage self‐directed control, children identify, and achieve goals by tracking contextual information and using this information to select relevant tasks. To disentangle the respective contributions of these processes, we manipulated the difficulty of context‐tracking via altering the presence or absence of contextual support (Study 1) and the difficulty of task selection by varying task difficulty (a)symmetry (Study 2) in 5–6 and 9‐10‐year‐olds, and adults. Results suggested that, although both processes contribute to successful self‐directed engagement of cognitive control, age‐related progress mostly relates to context‐tracking. Abstract : Keeping track of the context (context‐tracking) and selecting the relevant task (task selection) are key processes to autonomously attain goals. We investigated their developmental contributions to self‐directed cognitive control with two manipulations on the voluntary task‐switching paradigm. We observed that the context‐tracking manipulation differently affected children and adults, whereas the effects of the task selection manipulation were the same in all age groups. This suggested that improvements in self‐directed control engagement in childhood are mostly driven by progress in context‐tracking.